(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This article analyzes the theoretical foundations of developing students’ verbal-linguistic intelligence, as well as the methods, exercises, and practical tasks that contribute to its formation. Verbal-linguistic intelligence is explained through psychological and pedagogical approaches and is examined in connection with communicative skills, oral and written speech, and the culture of communication.